Bond strengths of four different dental gements: an in vitro study - Retief, Vasti (My University, 2014)
Standard practice in orthodontics has been the securing of stainless steel bands to posterior teeth using appropriate cements. Through the years different cements have been developed with varying properties. Some of the main requirements of orthodontic cements are: that the cement should attach the band to the tooth; should be sufficiently strong to withstand normal occlusal forces; and should prevent demineralization of enamel. For the latter reason, the inclusion of fluoride became standard, although this did not always enhance the other properties of the cement. The development of glass ionomer cement in 1969 by Wilson and Kent was thus a break-through for this formulation effected a slow fluoride release. The latest development in the field of orthodontic cements is the hybrid cements which are a combination of resin and glass ionomer in various ratios. This study sets out to evaluate some of the performance criteria of selected cements. The tensile bond strengths of four popular dental cements were tested when securing nonsandblasted and sandblasted stainless steel bands to extracted premolar teeth. The data for the four cements were compared, and the effect of sandblasting on tensile bond strength was established. Light microscopy examination was carried out on all the dislodged bands to establish the interface of fracture of the cement and how sandblasting affected the site of fracture. Mean bond strengths were found to be significantly greater when sandblasted stainless steel bands were used. Sandblasting had the greatest effect on the tensile bond strength of the hybrid cement,OptiBand. How ever this cement recorded low levels of tensile bond strengths in this study and even when sandblasted bands were used, was less effective than that of the next weakest cement (zinc oxyphosphate), without sandblasting. This in vitro study found that glass ionomer cement has the highest tensile strength irrespective of sandblasting of the bands and OptiBand the lowest. The evaluation of adherence of residual cement to the stainless steel bands revealed that there was a significant difference between cements and that sandblasting the bands exerted a significant effect on the amount of cement adhering. It was found that OptiBand adheres the best to the stainless steel bands, whether sandblasted or not. Glass ionomer recorded the least residual adherence. In the clinical situation it is suggested that the glass ionomer cement remains the cement of choice because of its favourable tensile bond strength, its adherence to the tooth structure and its sustained release of fluoride.